Social Innovation in Education and Social Service Organizations. Challenges, Actors, and Approaches to Foster Social Innovation - Schröer, Andreas (Frontiers in Education, 2021)
Social innovation became a widely discussed topic in politics, science promotion and business development. Recent European and US economic policies have set aside significant funds to generate and foster social innovation. In view of current challenges such as digitization, Work 4.0, inclusion and social integration of migrants, the question of how organizations can be empowered to develop new and innovative approaches and service models is becoming increasingly urgent. This especially applies to organizations in the fields of education and social services. In education, implementing new ideas and concepts is usually discussed as educational reform, which mostly addresses changes in policy agendas with consequences for national and international education systems. The concept of social innovation however has a different starting point: the source of new ideas and services are identified new and emergent needs in society or needs that are conceptualized and understood that in the past. Such need-based perspectives might bring new impulses to the field of education. Therefore, this paper identifies important existing strands of social innovation research, which need to be considered in the emerging academic discourse on social innovation in education. Looking at social innovation through an education research lens reveals the close relation between learning, creativity, and innovation. Individuals, teams and even organizations learn, engage in creative problem solving to create new and innovative products and services. From an organizational education perspective, the questions arise, how social innovation emerges and even more important, how the process of developing social innovation can be supported. After a brief introduction in the concept of social innovation, the paper discusses therefore the loci, where social innovation emerges, social innovators, approaches to foster social innovation as well as promoting and hindering factors for social innovation.